Compact Device for Monitoring Electret Filter Performance via Electric Field Strength - Johanna Zikulnig; Martin Lenzhofer; Christoph Mayer; Günter Grabher; Tobias Berchtold; Jürgen Kosel (Advanced Sensor Research, 2025)
Abstract The performance of electret filters, widely used in various air filtration systems, can degrade over time due to environmental factors such as humidity and elevated temperatures. This study introduces a compact electric field sensor designed for quasi‐continuous monitoring of electret filter performance. The sensor measures the electric field strength of the filter, which correlates with its efficiency. Testing under various conditions demonstrates high specificity (0.93), sensitivity (0.8), and precision (0.89) in measuring electric field strength as an indicator of filter efficiency. Statistically significant p‐values (<0.01) confirm the sensor's accuracy. The developed device can be integrated into various filtration systems, including smart masks, air conditioning, hospital ventilation units, and aircraft air purification systems, to ensure sustained performance and improved air quality in critical environments.